2014
DOI: 10.1161/circoutcomes.113.000555
|View full text |Cite
|
Sign up to set email alerts
|

Choice and Competition Between Adult Congenital Heart Disease Centers

Abstract: Background-Although concentrating adult congenital heart disease services at high-volume centers has been widely advocated, the potential beneficial effects of competition and patient choice have received relatively little attention. We aimed to assess the degree of patient choice and competition between adult congenital heart disease units and to investigate whether competition indices correlate with clinical quality or research output. Methods and Results-Competition between the 10 major adult congenital hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“… 58 Studies across other specialties have shown mixed results for the effect of fixed-price markets on improvements in health-care quality. 8 , 23 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 58 Studies across other specialties have shown mixed results for the effect of fixed-price markets on improvements in health-care quality. 8 , 23 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 …”
Section: Discussionmentioning
confidence: 99%
“…For each surgical centre we calculated a spatial competition index (SCI) as a measure of external competition. 22 , 23 The SCI provides a uniform metric that can be used across all surgical centres and that represents the demand for services and the availability of alternative hospitals. Across England, there is variation in the concentration of available hospitals depending on the degree of urbanisation or rurality.…”
Section: Methodsmentioning
confidence: 99%
“…Although it is rarely considered when establishing transfusion centres, spatial competition is potentially a driver in blood provision. Highly competitive facilities have also been linked to improved clinical outcomes for adult congenital heart disorders in [ 54 ], highlighting the importance of taking spatial competition into account in future research. However, our study used a small sample size of transfusing facilities hence future research could explore spatial competition with an increased sample size preferably a nation-wide coverage.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of spatial competition in the county healthcare market was defined within facility catchment constrained to 1-h travel time, optimal for emergency BT patients [ 54 ]. Spatial competition index (SCI) was computed for each facility to represent the level of service demand and availability of alternative facilities within the defined facility catchment.…”
Section: Methodsmentioning
confidence: 99%
“…Improving access to specialized CHD care is another important measure of quality particularly for people living in remote areas. Even among high income countries, there are significant geographic disparities in accessing specialized CHD healthcare (73,74). In middle-and low income countries, the problem tends to be even greater, since allocated resources are limited, despite the growing number of children born with CHD requiring specialized care (75).…”
Section: Towards Precision Healthmentioning
confidence: 99%